2009
DOI: 10.1007/s10661-009-1219-8
|View full text |Cite|
|
Sign up to set email alerts
|

Determining recreational, scenic, and historical–cultural potentials of landscape features along a segment of the ancient Silk Road using factor analyzing

Abstract: Generally, roads are structures connecting areas of special importance to each other (e.g., from urban areas to villages). In addition to functioning as transportation mediums, roads have aesthetic qualities by means of their recreational, scenic, and cultural functions. One of these unexplored roads, the Trabzon-Gümüşhane old state highway in the Northeast Turkey, the subject of this study, is quite unique for being a part of the historical Silk Road. The aim of the study is to determine the recreational, sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Landscape design intensity was regarded as relative to preference because it has been found to be significantly related to visual aesthetic quality [22]. Landscapes with proper design intensity may improve visual aesthetic quality, thereby promoting recreational activities, attracting tourists [23] and contributing to human mental health [24]. Xu et al demonstrated that people prefer natural or restored landscapes with moderate levels of design intensity [22].…”
Section: Landscape Design Intensitymentioning
confidence: 99%
“…Landscape design intensity was regarded as relative to preference because it has been found to be significantly related to visual aesthetic quality [22]. Landscapes with proper design intensity may improve visual aesthetic quality, thereby promoting recreational activities, attracting tourists [23] and contributing to human mental health [24]. Xu et al demonstrated that people prefer natural or restored landscapes with moderate levels of design intensity [22].…”
Section: Landscape Design Intensitymentioning
confidence: 99%
“…Aesthetic landscapes form a significant part of a community's cultural heritage (Jessel, 2006). An ecosystem with a high aesthetic value has a significant impact on social well-being (Kurdoglu and Kurdoglu, 2010). When people have a positive experience of an ecosystem aesthetic, they are more inclined to protect it against degradation (Gobster et al, 2007).…”
Section: The Most Important Social Well-being Indices and Ecosystem Services Under Degradation Impactmentioning
confidence: 99%
“…Although these studies mostly focus on the landscape outside settlements, their results may be indicative of the values of aesthetic quality in rural and exurban landscapes. Kates (1967), Kurdoglu and Kurdoglu (2010) and Tveit (2009) maintain that an aesthetically valuable environment has a significant impact on people's well-being. According to Jessel (2006), the aesthetic quality of landscapes forms a substantial part of the cultural heritage.…”
Section: Rural Landscapes and Their Identitymentioning
confidence: 99%